2018
DOI: 10.1007/978-3-319-98932-7_13
|View full text |Cite
|
Sign up to set email alerts
|

Character N-Grams for Detecting Deceptive Controversial Opinions

Abstract: Controversial topics are present in the everyday life, and opinions about them can be either truthful or deceptive. Deceptive opinions are emitted to mislead other people in order to gain some advantage. In the most of the cases humans cannot detect whether the opinion is deceptive or truthful, however, computational approaches have been used successfully for this purpose. In this work, we evaluate a representation based on character n-grams features for detecting deceptive opinions. We consider opinions on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Cardoso et al [7] evaluated content-based classification methods, revealing a temporal shift in data features that affected model performance over time. Sánchez-Junquera et al [8] proposed a method using n-gram features, outperforming some methods in identifying fake reviews but falling short when compared to alternative approaches.…”
Section: A Fake Review Detection Using Classical Statistical Machine ...mentioning
confidence: 99%
“…Cardoso et al [7] evaluated content-based classification methods, revealing a temporal shift in data features that affected model performance over time. Sánchez-Junquera et al [8] proposed a method using n-gram features, outperforming some methods in identifying fake reviews but falling short when compared to alternative approaches.…”
Section: A Fake Review Detection Using Classical Statistical Machine ...mentioning
confidence: 99%
“…Sánchez-Junquera, et al [139] proposed a fake review detection model based on the character n-gram feature. They used a support vector machine and Naïve Bayes as classification algorithms.…”
Section: ) Traditional Statistical Supervised Learning In Detecting Fake Rreviewsmentioning
confidence: 99%
“…More sophisticated features, such as deep syntactic patterns (Feng et al, 2012), argumentative features (Cocarascu and Toni, 2016), and word embeddings (Ren and Ji, 2017), were also successfully evaluated. More recently, the character n-grams features have shown a good trade-off between simplicity and performance for detecting deception in online reviews and essays on controversial topics (Cagnina and Rosso, 2017;Sánchez-Junquera et al, 2018). All these works found that both content and style are important factors to distinguish deception from truth.…”
Section: Related Workmentioning
confidence: 99%